2016
DOI: 10.1038/srep29931
|View full text |Cite
|
Sign up to set email alerts
|

Lupin Peptides Modulate the Protein-Protein Interaction of PCSK9 with the Low Density Lipoprotein Receptor in HepG2 Cells

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has been recently identified as a new useful target for hypercholesterolemia treatment. This work demonstrates that natural peptides, deriving from the hydrolysis of lupin protein and absorbable at intestinal level, are able to inhibit the proteinprotein interaction between PCSK9 and the low density lipoprotein receptor (LDLR). In order to sort out the best potential inhibitors among these peptides, a refined in silico model of the PCSK9/LDLR interaction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 69 publications
8
101
0
Order By: Relevance
“…Furthermore, these peptides may be absorbed in the small intestine, as they are transferred from the apical to the basolateral compartment in differentiated Caco-2 cells grown in a two-compartment system (Lammi et al, 2016a). A study in mildly hypercholesterolaemic subjects demonstrated that the level of circulating proprotein convertase subtilisin/kexin type 9 (PCSK9), which regulates low-density lipoprotein receptor levels and function, was significantly reduced after a 4-week consumption of a lupine protein isolate (30 g protein d À1 ) (Lammi et al, 2016b). In this context, the combined lupine protein isolation and its P. acidilactici-induced degradation can be a promising technology for increasing the low molecular weight units in protein isolates and ensuring higher bioavailability and direct desirable physiological effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these peptides may be absorbed in the small intestine, as they are transferred from the apical to the basolateral compartment in differentiated Caco-2 cells grown in a two-compartment system (Lammi et al, 2016a). A study in mildly hypercholesterolaemic subjects demonstrated that the level of circulating proprotein convertase subtilisin/kexin type 9 (PCSK9), which regulates low-density lipoprotein receptor levels and function, was significantly reduced after a 4-week consumption of a lupine protein isolate (30 g protein d À1 ) (Lammi et al, 2016b). In this context, the combined lupine protein isolation and its P. acidilactici-induced degradation can be a promising technology for increasing the low molecular weight units in protein isolates and ensuring higher bioavailability and direct desirable physiological effects.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results, we hypothesised that the bioavailability of lupine seed protein could be affected by the activity of trypsin inhibitors, the free amino acids (AAs) profile, biogenic amines (BAs), antioxidant capacity of the substrate, isoflavone content and the molecular weight of new peptides formed and their properties, among others. The tryptic and peptic peptides derived from lupine protein hydrolysis were shown to modulate cholesterol metabolism (Lammi et al ., ,b,c). Due to their health‐enhancing attributes and resultant selective, effective, safe and good tolerance once consumed, plant‐derived bioactive peptides are commonly consumed as part of a healthy, balanced diet and are often incorporated in functional foods, pharmaceuticals and medicines (Hayes & Bleakley, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, similar features are shared by P5 and P7 , which are endowed by a net charge equal to −0.9 and −2 at pH 7.0, and have calculated pI values equal to 5 and 0.8, respectively. In addition, a MD simulation pointed out that all these peptides show γ‐turn conformations underlining their structural similarities (Lammi, Zanoni, Aiello, Arnoldi, & Grazioso, ). Also in this case the molecular modeling forecast was successful, since the experimental IC 50 values fell in the range 50.0–75.0 µM, being thus comparable with that of P7 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that the contribution of P3 to the global hypocholesterolemic activity of the basolateral solution may be probably only moderate. In fact, in a recent article, the P5 concentration in the basolateral solution was calculated to be 28.64 ± 0.43 ng/µL, corresponding to 11.5% of the total peptic peptides absorbed by Caco‐2 cells (Lammi, Zanoni, et al, ). So, even if they show similar spatial conformations, quantitative MS‐based assays and biochemical investigations revealed the different abilities of P5 and P3 to be absorbed by Caco‐2 cells and a different mechanism through which they are able to modulate the cholesterol metabolism in the HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Snapshots from the corresponding trajectories were extracted to compute the binding energy ∆ G with MM-GBSA, a computational method already applied in similar studies with positive results. 30,47,48 All the peptide-BoxA complexes were solvated in a water box with a minimum distance from the protein surface of 10 Å. The total charge of the system was neutralized adding a proper number of Cl -/Na + ions.…”
Section: Methodsmentioning
confidence: 99%